DAMPAK KEBIJAKAN PENGENAAN BEA MASUK ANTI DUMPING NILON FILM DARI REPUBLIK RAKYAT TIONGKOK, THAILAND DAN TAIWAN TERHADAP INDUSTRI DALAM NEGERI - Alif Alfaini Rahman; Wulan Nur Intan Mawarni (Fakultas Ilmu Sosial dan Humaniora, 2025)
The Anti-Dumping Duty Policy is based on the principles of the General Agreement on Tariffs and Trade (GATT) 1994 and the World Trade Organization (WTO) Anti-Dumping Agreement, which allow member countries to take protective measures if proven dumping causes losses to Domestic Industries (DI). Normatively, this policy aligns with the objectives of protecting domestic industries and the principles of fair trade. However, its effectiveness is still often evaluated through indicators of accuracy, socialization, and achievement of objectives. This evaluation aims to show the potential positive impact of anti-dumping duties, but data and analysis are needed to support the effectiveness of the policy as measured by the indicators set by the BMAD team. This research discusses the effectiveness of the Anti-Dumping Duty (BMAD) policy on the import of nylon film from the People's Republic of China, where the analysis refers to the provisions of Government Regulation Number 34 of 2011 concerning Anti-Dumping Measures, Minister of Finance Regulation Number 21 of 2025, as well as the recommendations of the Anti-Dumping Committee of Indonesia (KADI) in protecting the interests of the domestic industry. The secondary materials used are books, journals, articles, and related literature.